2021
DOI: 10.1177/1757975920984196
|View full text |Cite
|
Sign up to set email alerts
|

Supporting youth 12–24 during the COVID-19 pandemic: how Foundry is mobilizing to provide information, resources and hope across the province of British Columbia

Abstract: Foundry is a province-wide network of integrated health and social service centres for young people aged 12–24 in British Columbia (BC), Canada. Online resources and virtual care broaden Foundry’s reach. Its online platform – foundrybc.ca – offers information and resources on topics such as mental health, sexual wellness, life skills, and other content suggested by youth and young adults. The COVID-19 pandemic has presented significant and unique challenges to the youth and their families/caregivers served by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…A WHO survey conducted in June–August 2020 indicated that more than two-thirds of mental health services globally were disrupted, especially school—and workplace-based mental health programs (World Health Organization, 2020 ). Although several digital adaptations and interventions have been implemented to support the mental health needs of young adults during the COVID-19 pandemic (Davenport et al, 2020 ; Zenone et al, 2021 ), several challenges remain for health services to provide virtual mental health support activities (e.g., telemedicine, online therapy) such as difficulty to reach people in need, develop quality services, and support to scale up those interventions (Bergin et al, 2020 ). For instance, technological and accessibility issues (e.g., poor internet connection, security concerns, safe private space) as well as lack of human connection (i.e., facilitating engagement and communication in a remote therapeutic relationship) were described as key barriers for accessing virtual mental health services by both clinicians and young adults (Hawke, Sheikhan, MacCon, & Henderson, 2021 ; Nicholas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…A WHO survey conducted in June–August 2020 indicated that more than two-thirds of mental health services globally were disrupted, especially school—and workplace-based mental health programs (World Health Organization, 2020 ). Although several digital adaptations and interventions have been implemented to support the mental health needs of young adults during the COVID-19 pandemic (Davenport et al, 2020 ; Zenone et al, 2021 ), several challenges remain for health services to provide virtual mental health support activities (e.g., telemedicine, online therapy) such as difficulty to reach people in need, develop quality services, and support to scale up those interventions (Bergin et al, 2020 ). For instance, technological and accessibility issues (e.g., poor internet connection, security concerns, safe private space) as well as lack of human connection (i.e., facilitating engagement and communication in a remote therapeutic relationship) were described as key barriers for accessing virtual mental health services by both clinicians and young adults (Hawke, Sheikhan, MacCon, & Henderson, 2021 ; Nicholas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, systemic and policy barriers were identified in both cases given that the two main forms of virtual care are evident in both Scotland in the United Kingdom and British Columbia in Canada: the first being virtual healthcare service delivery (eg, assessment, consultation, and education), 27 , 28 and the second type concerns provision of health-related information via virtual platforms (eg, websites and social media). 29 The case studies in both the United Kingdom and Canada, supported by a growing literature, suggest similar potential systematic and political barriers that health leadership and management need to pay attention to effect positive digital change and innovation in health service provision.…”
Section: Discussion: a Cross-case Analysismentioning
confidence: 99%
“…In the province of BC, Foundry is an integrated youth service (IYS) in the community that provides care (including MHSU services) for young people ages 12–24 years [ 11 ]. There are currently eleven centres across BC, with twelve more in development, and a provincial virtual care service [ 19 ]. Foundry has five core service streams, including mental health, substance use, peer support, primary care, and social services.…”
Section: Methodsmentioning
confidence: 99%